Characteristics of the Sharia Supervisory Board (SSB) and Investment Account Holders (IAH) to Islamic Social Responsibility Disclosure (ISRD) in Islamic Banks - Hirdinah Dewi Kenangsari; Falikhatun (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study examines the effect of education level on the Sharia Supervisory Board (SSB), SSB doctoral ratio, and Investment Account Holders (IAH) on Islamic Social Responsibility Disclosure (ISRD) using the control variable of profitability and firm size. The object of the research is Islamic banks in the four countries with the highest percentage of poor people in the selected regional division of Asia and Europe: Indonesia (Southeast Asia), Bangladesh (South Asia), Jordan (West Asia), and Turkey (Southeast Europe), which published annual reports in 2013-2019. The results showed that SSB education level and firm size positively affected ISRD, while IAH and profitability did not affect ISRD. Meanwhile, SSB doctoral ratio has a negative effect on ISRD. This research can provide consideration and input for Islamic Bank regulators in evaluating existing regulations. Future research is expected to add proxies for SSB characteristics and other variables in testing the effect of Islamic bank ISRD quality.